1994
DOI: 10.1017/s0950268800057393
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction for salmonella virulence–associated plasmid genes detection: a new tool in salmonella epidemiology

Abstract: SUMMARYThe important role of plasmid genes in assessing virulence for BALB/c mice in salmonella, and the difficulty of using standard techniques to detect them, led us to develop a detection method by gene amplification.One hundred and forty-three strains (71 serovars) of salmonella and 35 strains of other species were tested using specific oligonucleotide primers. The amplification products were identified by a specific oligonucleotide probe. Forty-nine salmonella strains from ten serovars (S. abortus ovis, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Various sets of primers for PCR detection of salmonellae have been described previously (14,18,19,24,29,30,31). Gooding and Chaudary (17) recently conducted a comparison study of primers with different test panels of Salmonella and non-Salmonella strains and different PCR conditions and found that there were variations with regard to the specificities of the primers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various sets of primers for PCR detection of salmonellae have been described previously (14,18,19,24,29,30,31). Gooding and Chaudary (17) recently conducted a comparison study of primers with different test panels of Salmonella and non-Salmonella strains and different PCR conditions and found that there were variations with regard to the specificities of the primers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most promising methods for detecting salmonellae is based on the PCR, which combines simplicity with specificity and sensitivity for detecting the pathogens in food. Several PCR assays have been developed by targeting various Salmonella genes, such as invA (29,31), 16S rRNA (19), agfA (14), and viaB (18), and virulence-associated plasmids (24,30). These PCR assays are used mainly for detecting salmonellae in poultry, meat, and milk samples (5,7,13,22).…”
mentioning
confidence: 99%
“…On the other hand, several PCR assays have been developed to detect Salmonella at genus and serotype level on different areas of the genome. Selected regions that have been studied singly or combined for PCR assay include agf A, fim A, hin , H‐li, iag AB , IS 200, iro B, mkf A, omp C, spv R , via B, (Cano et al., 1993; Fluit et al., 1993; Mahon and Lax, 1993; Way et al., 1993; Rexach et al., 1994; Chevrier et al., 1995; Hashimoto et al., 1995; Cohen et al., 1996; Doran et al., 1996; Kwang et al., 1996; Baumler et al., 1997). Some of these methods have limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Hin and H‐li genes are specific for motile strains not for Salmonella Gallinarum and Salmonella Pullorum (Way et al., 1993) . Amplification of mkf A showed positive results only from 10 Salmonella serovars (Rexach et al., 1994). For specific identification of S. Typhimurium target genes such as florfenicol (flo), invasion ( inv‐ A), integron (int ) and, virulence ( spv C) have been used (Bolton et al., 1999; Khan et al., 2000; Ebner and Mathew, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Constant variations in dietary habits and agronomic practices, the increase in the consumption of vegetables that are consumed raw along with increased importation of fresh produce supposedly contribute to increase in the number of outbreaks associated with vegetables and animal feed of vegetable origin (Altekruse, Cohen, & Swerdlow, 1997). Salmonella outbreaks have been linked to tomatoes (Centers for Disease Control and Prevention, 1993), seed sprouts (Mahon et al, 1997;O'Mahony et al, 1990), watermelons (Blostein, 1991;Centers for Disease Control and Prevention, 1979;Centers for Disease Control and Prevention, 1979), and animal feeds (Gooding & Choudary, 1999;Rexach, Dilasser, & Fach, 1994). Disposal of treated wastewater for agricultural irrigation simultaneously solves water shortage problems and reduces potential environmental contamination.…”
Section: Introductionmentioning
confidence: 99%